HÜZÜN – TURKISH MELANCHOLY IN ORHAN PAMUK’S STAMBUL - Szalewska, Katarzyna (Porównania, 2014)
The article is a reflection on the fictionalized essay Istanbul: Memories and the City by Orhan Pamuk, which is analyzed here in the context of the entire works of the Turkish Nobel Prize winner. All Pamuk’s novel are consistently maintained in the mood of nostalgia for the past, searching for the mystery, and their protagonist is the space of Istanbul. In this essay, the author defines the melancholy, to which he discursievely continually returns, as hüzün as a special kind of sadness appropriate for the Turkish culture. The purpose of this article is therefore to describe this phenomenon using comparative recognition, reflection on the experience of the past in contemporary historical culture, and also tools of humanistic geography. Hüzün then appears as a kind of melancholy of a place, but also as a special form of melancholic writing.